Metacognitive online reading and navigational strategies by science and technology university students - Ruhil Amal, Azmuddin; Nor Fariza , Mohd Nor; Afendi , Hamat (Universiti Kebangsaan Malaysia, 2017)
Reading has taken a new dimension, where students in higher institutions are consistently required to read massive amounts of online materials to gain knowledge, complete tasks and assignments. Hence, the ability to read online effectively is becoming increasingly important, as students need to utilize, understand and respond to online materials. However, most university undergraduates lack the ability to read effectively and critically. Therefore, the present study examines university students’ metacognitive online reading strategies and navigational strategies in reading English Science and Technology hypertexts for academic purposes. Data were collected through an online survey among 55 Science and Technology students in a public university situated in the east coast of peninsular Malaysia to identify the most frequent metacognitive online reading strategies used by the students. The survey revealed that students used problem-solving strategies the most followed by global and support reading strategies. Out of the same sample, 12 students were purposively selected to be a part of qualitative data collection on navigational strategies that was conducted through individual screen recordings captured through a screen recording software. The software recorded the on-screen activities while students were using an interactive reading system named iREAD; Interactive Reading for Academic Disciplines. Based on the screen recordings, it can be observed that students mostly used mixed overview strategies followed by serial overview strategies, and serial navigational strategies when reading online materials. The findings concluded the need to teach students metacognitive awareness in order to read online materials successfully to make learning more efficient, meaningful and beneficial.